Clinical experience with the oxygen concentrator. Issue 6390 (13th August 1983) - Evans, T W; Waterhouse, J; Howard, P
Abstract : The oxygen concentrator is an accepted means of delivery of long term domiciliary oxygen treatment. Conditions of use, however, need to be carefully defined. Fourteen concentrators were used for one year by patients with hypoxaemic chronic obstructive airways disease, and mechanical reliability, patient compliance with a regimen of 15 hours' use a day, smoking habits, and variation in arterial gas tensions studied. Though many patients failed to achieve either the desired daily use or the recommended arterial oxygen tension, problems were generally minor and could probably be overcome by careful supervision and planning. Overall the concentrator appeared to be the most economical means of providing oxygen treatment at home and was much preferred by patients who had previously used oxygen cylinders.